A ratiometric styryl bridging triphenylamine-indolinium based fluorescent dye for detection of cyanide with a large emission shift in human breast cancer cells and test strips. Issue 10 (3rd October 2021) - Mandal, Moumi; Karak, Anirban; Halder, Satyajit; Banerjee, Shilpita; Maiti, Anwesha; Jana, Kuladip; Mahapatra, Ajit Kumar; Kar, Arik
ABSTRACT: A new type of styryl bridging triphenyl amine-indolium conjugated dye has been developed for the colorimetric and ratiometric detection of cyanide. The detection of cyanide is confirmed by means of the fast nucleophilic attack of cyanide by the indolium group of the probe that results a speedy sensing process for cyanide with clear color and fluorescence change of the ICT process. The ratiometric fluorescence changes illustrated a linear response in the range of 0-18 μM with a low LOD value (1.7×10-7 M-1). The as-reported sensor not only function as a colorimetric sensor for "in-the-field" measurement by virtue of a "dip-stick" approach but also interact with a human breast cancer cell (MDA-MB 231) which reveals the realistic value of this probe for tracking cyanide anions in biological systems. Graphical abstract: uf0001